2013
DOI: 10.3109/09637486.2013.806448
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity, total phenolics and nutritional content in selected ethiopian staple food ingredients

Abstract: The total antioxidant capacity, total phenolics content (TPC) and nutritional content of five types of enset (Enset ventricosum) flour in comparison with four staples (teff [Eragrostis tef], wheat, corn and tapioca) were evaluated. Teff, corn and "amicho" (corm of enset) had the highest ferric reducing antioxidant power (FRAP). The FRAP and TPC of teff (1.8 mmol Trolox equivalence/100 g dry matter (DM) and 123.6 mg gallic acid equivalent/100 g DM, respectively) were over 4-fold larger than the lowest obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
59
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 35 publications
12
59
5
1
Order By: Relevance
“…Soluble, bound, and total PCs of the tef grain varieties are given in Table I. Soluble PCs of unknown tef varieties that ranged from 829 to 1,147 mg of GAE/100 g db (Boka et al 2013) and 126 mg of GAE/100 g db (Forsido et al 2013) are much higher compared with what is reported here. There was a significant difference in soluble PCs among the varieties (P < 0.001).…”
Section: Resultscontrasting
confidence: 46%
See 1 more Smart Citation
“…Soluble, bound, and total PCs of the tef grain varieties are given in Table I. Soluble PCs of unknown tef varieties that ranged from 829 to 1,147 mg of GAE/100 g db (Boka et al 2013) and 126 mg of GAE/100 g db (Forsido et al 2013) are much higher compared with what is reported here. There was a significant difference in soluble PCs among the varieties (P < 0.001).…”
Section: Resultscontrasting
confidence: 46%
“…Boka et al (2013), Forsido et al (2013), and Salawu et al (2014) studied the antioxidant capacity of tef by taking samples of unknown tef varieties or tef flour. Boka et al (2013), Forsido et al (2013), and Salawu et al (2014) studied the antioxidant capacity of tef by taking samples of unknown tef varieties or tef flour.…”
mentioning
confidence: 99%
“…Teff had the highest ferric reducing antioxidant power (FRAP). The FRAP and TPC of teff (1.8mmol Trolox equivalence/100 g dry matter (DM) and 123.6mg gallic acid equivalent/100g DM, respectively) [26].…”
Section: Journal Of Food and Nutrition Researchmentioning
confidence: 99%
“…These compounds were isolated from Eragrostis genus for the first time. Antioxidant or neuroprotective activities of E. ferruginea and E. japonica might be mediated by the previously reported compounds, tricin, ageconyflavone A, nectandrin B, and 4-ketopinoresinol [5] and by the isolated compounds in this study, isoorientin (1), isovitexin (2), and caffeic acid (3), respectively. Antioxidant activity of E. curvula also might be induced by the previously reported flavones, tricin and violanthin [20].…”
Section: Neuroprotective Activity Assessmentmentioning
confidence: 93%
“…The methanol (MeOH) extracts from the flour of E. tef and E. tef varieties showed antioxidant activity using the 1,1-diphenyl-1-picrylhydrazyl radical scavenging activity (DPPH RSA) [1][2]. The hexane extract of E. viscosa presented moderate molluscicidal activity against the snail Biomphalaria glabrata and 4 diterpenoids were isolated from the extract [3].…”
Section: Previous Studiesmentioning
confidence: 99%